Socialization of Digital Leadership Capacity Building and Adaptive Organizational Culture for Educators in the Era of Education 4.0 at Bandung Percut Sei Tuan High School - Fahmi Ashari S. Sihaloho; Putri Mauliza; Henny Purnama Dewi; Nabila Tijani Tharifah (Outline Publisher, 2026)
The rapid advancement of the Education 4.0 era necessitates a fundamental transformation in the role of educators from conventional instructors to digital leaders capable of managing change, yet significant challenges persist regarding the readiness of human resources and the existence of rigid organizational cultures that resist technological integration. This community service activity aims to enhance the capacity of digital leadership and foster an adaptive organizational culture among educators at Senior High School Bandung Percut Sei Tuan. The implementation method utilized a participatory training approach involving thirty-five educators and administrative staff, encompassing needs assessment surveys, interactive workshops, conflict management simulations, and the formulation of follow-up plans for digital innovation. The effectiveness of the program was evaluated through a comparative analysis of pre-test and post-test scores as well as participant satisfaction assessments. The results indicated a significant increase in cognitive competence, marked by a rise in the average understanding score from 51.4 to 80.1, with the highest improvement observed in the aspect of digital leadership strategies at 62 percent. Qualitatively, the activity successfully minimized teacher resistance to technology and cultivated a culture of intergenerational collaboration through reverse mentoring initiatives. It is concluded that this socialization serves as an effective strategic step in preparing the mental readiness and work culture of the school to face the dynamics of sustainable digital transformation.